Liposomal paclitaxel induces apoptosis, cell death, inhibition of migration capacity and antitumoral activity in ovarian cancer - Faria, Raquel Santos (2021)
The main goal of this study is to evaluate the efficacy of the paclitaxel (PTX) drug formulated with a liposomal nanosystem (L-PTX) in a peritoneal carcinomatosis derived from ovarian cancer. In vitro cell viability studies with the human ovarian cancer line A2780 showed a 50% decrease in the inhibitory concentration for L-PTX compared to free PTX. A2780 cells treated with the L-PTX formulation demonstrated a reduced capacity to form colonies in comparison to those treated with PTX. Cell death following L-PTX administration hinted at apoptosis, with most cells undergoing initial apoptosis. A2780 cells exhibited an inhibitory migration profile when analyzed by Wound Healing and real-time cell analysis (xCELLigence) methods after L-PTX administration. This inhibition was related to decreased expression of the zinc finger E-box-binding homeobox 1 (ZEB1) and transforming growth factor 2 (TGF-β2) genes. In vivo L-PTX administration strongly inhibited tumor cell proliferation in ovarian peritoneal carcinomatosis derived from ovarian cancer, indicating higher antitumor activity than PTX. L-PTX formulation did not show toxicity in the mice model. This study demonstrated that liposomal paclitaxel formulations are less toxic to normal tissues than free paclitaxel and are more effective in inhibiting tumor cell proliferation/migration and inducing ZEB1/TGF-β2 gene expression.